Variation in Seed and Seedling Traits of Pongamia pinnata - Gupta, Garima; Handa, A. K.; Ajit,; Maurya, Deepak (Indian Forester, 2016)
An experiment was conducted at National Research Center For Agroforestry, Jhansi (situated between 24° 11 to 26°27'N latitude and 78° 17' to 81° 34'E longitudes, at an elevation of 300m amsl), to study the effect of seed source of Pongamia pinnata, on germination and seedling growth, which can be used in genetic improvement programme. The ten sources/ provenances were selected from Uttar Pradesh (Jhansi, Babina, Matateela, Faizabad), West Bengal (Kalyani, Jhargram, Haldia), Haryana (Hisar), Karnataka (Dharwar) and Andhra Pradesh (Hydrabad). The seeds from these sources were obtained either through survey or through coordinating centers of All India Coordinated Research Project on Agroforestry (AICRP on AF). Comparison of morphological characters among different seed sources revealed, that the seed source of Jhargram exhibited its superiority in seed and pod size. Seed length was found maximum in the seed collected from Kalyani. The germination and related parameters indicate that the provenance of Kalyani gave the significantly higher value for germination percentage, germination value and Germination energy index. The seedling growth parameters indicated that the provenance of Dharwar exhibited maximum growth and biomass of Pongamia pinnata in comparison to other provenance/ sources. Overall results exhibited that the seeds collected from West Bengal (Kalyani and Jhargram) performed constantly in term of germination, growth and biomass at nursery stage.